A Case Report in Health Information Exchange for Inter-organizational Patient Transfers - Richardson, J.E.; Malhotra, S.; Kaushal, R.; with the HITEC Investigators (Applied Clinical Informatics, 2014)
Objective: To provide a case report of barriers and promoters to implementing a health information exchange (HIE) tool that supports patient transfers between hospitals and skilled nursing facilities.Methods: A multi-disciplinary team conducted semi-structured telephone and in-person interviews in a purposive sample of HIE organizational informants and providers in New York City who implemented HIE to share patient transfer information. The researchers conducted grounded theory analysis to identify themes of barriers and promoters and took steps to improve the trustworthiness of the results including vetting from a knowledgeable study participant.Results: Between May and October 2011, researchers recruited 18 participants: informaticians, healthcare administrators, software engineers, and providers from a skilled nursing facility. Subjects perceived the HIE tool’s development a success in that it brought together stakeholders who had traditionally not partnered for informatics work, and that they could successfully share patient transfer information between a hospital and a skilled nursing facility. Perceived barriers included lack of hospital stakeholder buy-in and misalignment with clinical workflows that inhibited use of HIE-based patient transfer data. Participants described barriers and promoters in themes related to organizational, technical, and user-oriented issues.The investigation revealed that stakeholders could develop and implement health information technology that technically enables clinicians in both hospitals and skilled nursing facilities to exchange real-time information in support of patient transfers. User level barriers, particularly in the emergency department, should give pause to developers and implementers who plan to use HIE in support of patient transfers.Conclusions: Participants’ experiences demonstrate how stakeholders may succeed in developing and piloting an electronic transfer form that relies on HIE to aggregate, communicate, and display relevant patient transfer data across health care organizations. Their experiences also provide insights for others seeking to develop HIE applications to improve patient transfers between emergency departments and skilled nursing facilities.Citation: Richardson JE, Malhotra S, Kaushal R. A case report in health information exchange for inter-organizational patient transfers. Appl Clin Inf 2014; 5: 642–650http://dx.doi.org/10.4338/ACI-2014-02-CR-0016
Keywords: Medical informatics; patient transfer; health information exchange; computer communication networks; qualitative research